Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1118/1.598771
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo comparison of the response of the PTW-diamond and the TL-diamond detectors in megavoltage photon beams

Abstract: A detailed Monte Carlo study of the PTW-diamond solid state detector response in megavoltage photon beams (60Co gamma rays to 25 MV x rays) has been performed with the EGS4 Monte Carlo Code. The sensitive volume of the diamond detector is a disk of diameter 4.4 mm and thickness 0.40 mm. The phantom material was water and the irradiation depth was usually 3 cm but additional simulations were performed at six other depths for the 10 and 25 MV x rays. Results show that the PTW-diamond detector response per unit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…This experimental finding is based on the measure of the sensitivity factors ͑nC/Gy͒ in 6 MV and 25 MV photon beams and in 6 -10-15-22 MeV electron beams. For the photons, this result is confirmed by Mobit et al 2 who, with a Monte Carlo approach, predicted agreement between diamond dosimeter and ionization chamber in the depth dose measurements. Recently, Haryanto et al 3 reported output factors ͑OF͒, percentage depth doses ͑PDD͒ and transverse dose profiles measured with a PTW diamond detector in agreement with Monte Carlo calculations.…”
Section: Introductionsupporting
confidence: 74%
“…This experimental finding is based on the measure of the sensitivity factors ͑nC/Gy͒ in 6 MV and 25 MV photon beams and in 6 -10-15-22 MeV electron beams. For the photons, this result is confirmed by Mobit et al 2 who, with a Monte Carlo approach, predicted agreement between diamond dosimeter and ionization chamber in the depth dose measurements. Recently, Haryanto et al 3 reported output factors ͑OF͒, percentage depth doses ͑PDD͒ and transverse dose profiles measured with a PTW diamond detector in agreement with Monte Carlo calculations.…”
Section: Introductionsupporting
confidence: 74%
“…͑3͒ that accounts for the electron trajectory lengths within the chamber, as that length can be assumed to be proportional to the amount of ionization, and thus to the chamber output. In a recent study, Mobit et al 20 published Monte Carlo data about the direct photon response of a diamond detector. They specify the dose contribution from photon interaction in the cavity material, ␣ c , in terms of percentage, which they calculated in a simulated broad beam.…”
Section: Compton Electron Transportmentioning
confidence: 99%
“…In a recent study, Mobit et al 20 published Monte Carlo data about the direct photon response of a diamond detector. They specify the dose contribution from photon interaction in the cavity material, ␣ c , in terms of percentage, which they calculated in a simulated broad beam.…”
Section: Compton Electron Transportmentioning
confidence: 99%
See 2 more Smart Citations